THE EFFECT OF HYPNOSIS THERAPY ON THE PAIN SCALE OF POST OPERATIVE PATIENTS: LITERATURE REVIEW - Wasita, Rangga; Peristiowati, Yuly; Ellina, Agusta Dian; Fajriyah, Asruria Sani (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Background: Acute pain is a sensory or emotional experience associated with actual or functional tissue damage, with a sudden or slow onset and of mild to severe intensity lasting less than 3 months. Surgical procedures can cause acute pain. The main outcome of nursing interventions related to acute pain is a decrease in the level of pain. One of the non-pharmacologic nursing therapeutic interventions that can reduce pain levels and increase comfort is hypnosis therapy. Purpose: To determine the effect of hypnotherapy on pain scale in postoperative patients. Methods: Scientific articles in English and full texts published in 2002-2020 were identified and then analyzed by PI(E)O (problem; intervention; exposure; comparison; outcome). A total of 3404 articles from the PubMed, Wiley, Science Direct, and Google Scholar databases were identified using the keywords